2024
DOI: 10.1002/jmv.29424
|View full text |Cite
|
Sign up to set email alerts
|

RNA recognition by PKR during DNA virus infection

Ruilin Zhang,
John Karijolich

Abstract: Protein kinase R (PKR) is a double‐stranded RNA (dsRNA) binding protein that plays a crucial role in innate immunity during viral infection and can restrict both DNA and RNA viruses. The potency of its antiviral function is further reflected by the large number of viral‐encoded PKR antagonists. However, much about the regulation of dsRNA accumulation and PKR activation during viral infection remains unknown. Since DNA viruses do not have an RNA genome or RNA replication intermediates like RNA viruses do, PKR‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 133 publications
(239 reference statements)
0
2
0
Order By: Relevance
“…A further mechanistic study is warranted to dissect Alternol-induced activation of PERK and IRE1α cascades, although ROS dependency was confirmed (Li et al, 2021;Yang et al, 2024). PKR is one of the four eIF2α kinases (Jackson et al, 2010) and it is mainly activated after viral infection in mammalian cells (Park et al, 2006;Zhang and Karijolich, 2024). However, recent studies showed that PKR activation was also involved in eIF2α/ S51 phosphorylation and immunogenic cell death induced by chemo-drugs in melanoma and breast cancer cells (Giglio et al, 2018;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further mechanistic study is warranted to dissect Alternol-induced activation of PERK and IRE1α cascades, although ROS dependency was confirmed (Li et al, 2021;Yang et al, 2024). PKR is one of the four eIF2α kinases (Jackson et al, 2010) and it is mainly activated after viral infection in mammalian cells (Park et al, 2006;Zhang and Karijolich, 2024). However, recent studies showed that PKR activation was also involved in eIF2α/ S51 phosphorylation and immunogenic cell death induced by chemo-drugs in melanoma and breast cancer cells (Giglio et al, 2018;Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PKR is one of the four eIF2α kinases ( Jackson et al, 2010 ) and it is mainly activated after viral infection in mammalian cells ( Park et al, 2006 ; Zhang and Karijolich, 2024 ). However, recent studies showed that PKR activation was also involved in eIF2α/S51 phosphorylation and immunogenic cell death induced by chemo-drugs in melanoma and breast cancer cells ( Giglio et al, 2018 ; Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%